A Metal‐free Approach to 3‐Aryl‐3‐hydroxy‐2‐oxindoles by Treatment of 3‐Acyloxy‐2‐oxindoles with Diaryliodonium Salts. Issue 2 (3rd November 2015) - Li, Xiaokang; Ni, Wei; Mao, Fei; Wang, Wei; Li, Jian
Abstract: A mild, metal‐free approach has been realized for the facile construction of highly valuable 3‐(hetero)aryl‐3‐hydroxy‐2‐oxindoles. Direct arylations of 3‐acyloxy‐2‐oxindoles with diaryliodonium salts as arylation reagents are implemented in the presence of K2 CO3 at room temperature without using an organometallic promoter to deliver an array of 3‐(hetero)aryl‐3‐hydroxy‐2‐oxindoles in good yields. Abstract : A new family member : A simple and efficient method for direct arylation of 3‐acyloxy‐2‐oxindoles has been developed. Direct arylations of 3‐acyloxy‐2‐oxindoles with diaryliodonium salts as arylation reagents are implemented in the presence of K2 CO3 at room temperature without using an organometallic promoter to deliver an array of 3‐(hetero)aryl‐3‐hydroxy‐2‐oxindoles in good yields.